2018
DOI: 10.1002/aic.16182
|View full text |Cite
|
Sign up to set email alerts
|

Ethane‐selective carbon composites CPDA@A‐ACs with high uptake and its enhanced ethane/ethylene adsorption selectivity

Abstract: Novel composites (CPDA@A‐ACs) of carbonized polydopamine (CPDA) and asphalt‐based activated carbons (A‐ACs) were successfully synthesized, and characterized for adsorption separation of ethane/ethylene. The resulting CPDA@A‐ACs exhibited high Brunauer–Emmett–Teller surface area of 1971 m2/g. The O and N contents on CPDA@A‐ACs are higher than those on A‐ACs due to the introduction of CPDA. Interestingly, CPDA@A‐ACs exhibited great preferential adsorption of ethane over ethylene. Its ethane capacity reached as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…From the data presented in Figure 7, it is clear that the CH 4 uptake exhibited by SC‐6 is the highest among the reported porous carbons, and also much higher than most of MOFs, which can likely be attributed to abundant ultramicropores (<0.8 nm) present in SC‐6. Ultramicropores of molecular dimensions play a significant role in the adsorption of small gas molecules 40‐42 . The ultramicropore volume of SC‐6 is as high as 0.25 cm 3 /g, constituting 78% of the micropore volume.…”
Section: Resultsmentioning
confidence: 99%
“…From the data presented in Figure 7, it is clear that the CH 4 uptake exhibited by SC‐6 is the highest among the reported porous carbons, and also much higher than most of MOFs, which can likely be attributed to abundant ultramicropores (<0.8 nm) present in SC‐6. Ultramicropores of molecular dimensions play a significant role in the adsorption of small gas molecules 40‐42 . The ultramicropore volume of SC‐6 is as high as 0.25 cm 3 /g, constituting 78% of the micropore volume.…”
Section: Resultsmentioning
confidence: 99%
“…For carbonaceous adsorbents, the selectivity toward ethane is usually harnessed by the interactions between ethylene and polar heteroatom content of the carbon surface, like oxygen and nitrogen. The carbonaceous adsorbents were synthesized from the precursor of fructose (Xiao et al, 2018) for oxygen functionalized carbon and polydopamine (Liang et al, 2018) or glucosamine (Wang et al, 2019a(Wang et al, , 2019b for nitrogen -doped carbon. IAST-based selectivity of ethane over ethylene was reported to be as high as (Liang et al, 2018) 20 in the lowest pressure and ethane to ethylene ratio of 1:15.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…The carbonaceous adsorbents were synthesized from the precursor of fructose (Xiao et al, 2018) for oxygen functionalized carbon and polydopamine (Liang et al, 2018) or glucosamine (Wang et al, 2019a(Wang et al, , 2019b for nitrogen -doped carbon. IAST-based selectivity of ethane over ethylene was reported to be as high as (Liang et al, 2018) 20 in the lowest pressure and ethane to ethylene ratio of 1:15. DFT calculations revealed that (Liang et al, 2018;Wang et al, 2019aWang et al, , 2019b pristine sp 2 hybridized carbon surface favors ethylene adsorption owing to the pp interactions between ethylene and delocalized p bond of carbon.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Second, relative to ethane, ethylene has greater concentration in cracked gas (ethane/ethylene = 1:9–15). Thus, using ethylene‐selective MOFs will require more adsorbents and larger fix‐bed volume compared to using ethane‐selective MOFs . Third, the use of ethylene‐selective MOFs means additional ethylene desorption processes (achieved by thermal or vacuum treatment) to obtain the target product ethylene (Figure S1a).…”
Section: Introductionmentioning
confidence: 99%